Draft Annual Plan 2008-09 West Bengal Development and Planning Department - Planning Commission (Planning Commission, 2008)
The importance of agriculture in State’s economy is reflected by its contribution of about 20% to the total SDP(at constant price) and by its support to employment of nearly 58% of its rural work-force. It is relevant to state that despite remarkable progress in overall production and productivity,the growth rate of agriculture has been steadily declining since early 1990. Considering all these crucial aspects, critical areas have been identified and related developmental schemes have accordingly been proposed launched from the inception of the Annual Plan, 2007-08. The main focus has been concentrated on the red and laterite and other problematic areas with region-specific schemes of 30- 40% plan outlay. For watershed development and reclamation of degraded/waste lands the schemes are best implemented with greater emphasis. For capacity building among farm women, a new scheme has been designed. Agriculture related education, innovative and commodity research and extension revitalization are being provided. Programmes have been worked out to cover all the blocks with meteorological observatories and introducing new schemes of e-governance in agriculture sector and IT facilities up to block level . The emphasis is also being laid on disaster management programme and crop insurance schemes.
Draft Annual Plan 2008-09
Government of West Bengal